2020
DOI: 10.1177/0269215520932196
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of extracorporeal shock wave therapy for improving upper limb spasticity and functionality in stroke patients: a systematic review and meta-analysis

Abstract: Objective: To assess the effectiveness of Extracorporeal Shock Wave Therapy for reducing spasticity and improving functionality of the upper limb in stroke survivors. Data sources: A systematic review of MEDLINE, Cochrane Central Register of Controlled Trials, CINAHL, PEDro, REHABDATA, Scielo, Scopus, Web of Science, Tripdatabase and Epistemonikos from 1980 to April 2020 was carried out. Review methods: The bibliography was screened to identify randomized controlled clinical trials that applied extracorporeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
0
29
1
Order By: Relevance
“…At present, in the Rehabilitation Treatment (RT) of stroke patients with hemiplegia, various rehabilitation techniques based on the concepts and theories of Bobath, Rood, Brunnstrom and Proprioceptive Neuromuscular Facilitation (PNF) are the primary rehabilitation training methods. Recently, an increasing number of novel treatments have been applied to the rehabilitation of stroke patients with upper limb motor dysfunction, including Virtual Reality (VR), 5 Brain-machine Interface (BI), 6 Mental Practice (MP), 7 extracorporeal shock wave therapy, 8 music therapy 9,10 and so on. However, the effect of these novel treatments in clinical practice has not been fully verified.…”
Section: Introductionmentioning
confidence: 99%
“…At present, in the Rehabilitation Treatment (RT) of stroke patients with hemiplegia, various rehabilitation techniques based on the concepts and theories of Bobath, Rood, Brunnstrom and Proprioceptive Neuromuscular Facilitation (PNF) are the primary rehabilitation training methods. Recently, an increasing number of novel treatments have been applied to the rehabilitation of stroke patients with upper limb motor dysfunction, including Virtual Reality (VR), 5 Brain-machine Interface (BI), 6 Mental Practice (MP), 7 extracorporeal shock wave therapy, 8 music therapy 9,10 and so on. However, the effect of these novel treatments in clinical practice has not been fully verified.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies ( 48 50 ) have shown that ESWT may improve the muscle spasm of stroke patients without serious adverse reactions. A meta-analysis ( 51 ) found that adding the ESWT to conventional therapy provides an additional benefit for reducing upper limb spasticity, and the results may be optimal given the ESWT at the subacute phase, but the mechanism remains unclear. Many studies conducted in recent years have been investigating the biological effects of ESWT ( 52 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…14−16 A recent meta-analysis reviewed 16 randomized controlled trials (RCTs) of stroke patients, and reported that ESWT was effective in reducing upper-limb spasticity for more than 12 weeks. 17 Another meta-analysis demonstrated that the beneficial effects of ESWT in alleviating lower-limb spasticity could last for more than four weeks. 18 Compared with BoNT injections, ESWT is a non-drug therapy and does not elicit neuromuscular denervation.…”
Section: Introductionmentioning
confidence: 99%